Atores em disputa de sentidos: jornalismo e homofobia nas narrativas da Folha de São Paulo e O Globo - Carlos Alberto de Carvalho (2010)
The extent to which homophobia - the complex reality deeply rooted in our culture - is challenging for the notions of journalism as a social actor, from the perspective of the agent who constantly negotiates the possible meanings of the events reported with other social actors, is the central objective of this thesis. We took into account some historical and theoretical definitions of homophobia, which follow discussions about journalism as a social actor. As a social actor, the dispute in which journalism is involved reflects on the production of narrative frameworks that promote the events reported. Therefore, we introduce the concepts of framing, event and narrative, so that we can understand more the ways they carry out the coverage of events related to homophobia and people affected by it in the newspaper Folha de S. Paulo and O Globo, from February 18 to August 18, 2008.